2020
DOI: 10.1186/s13148-020-00974-7
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced and genetically inherited obesity differentially alters DNA methylation profile in the germline of adult male rats

Abstract: Background Paternal obesity has been associated with reduced live birth rates. It could lead to inheritance of metabolic disturbances to the offspring through epigenetic mechanisms. However, obesity is a multifactorial disorder with genetic or environmental causes. Earlier we had demonstrated differential effects of high-fat diet-induced obesity (DIO) and genetically inherited obesity (GIO) on metabolic, hormonal profile, male fertility, and spermatogenesis using two rat models. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 70 publications
(99 reference statements)
0
27
0
Order By: Relevance
“…In our present study, paternal obesity has been associated with low average litter weight. Previous study has demonstrated that paternal obesity induced by high-fat diet can affect offspring metabolic by means of epigenetic mechanisms ( 58 ). A recent work demonstrated paternal exposure to type 2 diabetes mediates intergenerational and transgenerational effects on the reproductive health of the offspring, especially on sperm quality ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, paternal obesity has been associated with low average litter weight. Previous study has demonstrated that paternal obesity induced by high-fat diet can affect offspring metabolic by means of epigenetic mechanisms ( 58 ). A recent work demonstrated paternal exposure to type 2 diabetes mediates intergenerational and transgenerational effects on the reproductive health of the offspring, especially on sperm quality ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggest that high-fat diet intake could alter the DNA methylation profile in the germline of adult male rats and that could partially transmit the altered epigenetic signatures of developmental importance via sperm to the embryo causing embryo loss ( Deshpande et al, 2020 ). It is known that high-fat diet intake increases adiposity in the individual per se and several studies focusing on reproductive health have shown that either maternal or paternal high-fat diet intake is able to program increased adiposity in male offspring, besides increasing adiposity in the progenitors ( Palmer et al, 2012 ; Fullston et al, 2013 ; Fan et al, 2018 ; Deshpande et al, 2020 ; Sertorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggest that high-fat diet intake could alter the DNA methylation profile in the germline of adult male rats and that could partially transmit the altered epigenetic signatures of developmental importance via sperm to the embryo causing embryo loss ( Deshpande et al, 2020 ). It is known that high-fat diet intake increases adiposity in the individual per se and several studies focusing on reproductive health have shown that either maternal or paternal high-fat diet intake is able to program increased adiposity in male offspring, besides increasing adiposity in the progenitors ( Palmer et al, 2012 ; Fullston et al, 2013 ; Fan et al, 2018 ; Deshpande et al, 2020 ; Sertorio et al, 2021 ). Our model showed that high-fat and high-sugar diet intake increased the adipose tissue weight in both progenitors and that there was an interaction effect of maternal and paternal diet intake increased adiposity of retroperitoneal and epididymal adipose tissue in adult male offspring, evidencing the synergistic effect of the paternal and maternal diets combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-fat diet reduces global genomic DNA methylation levels in the sperm and in the spermatozoa of the offspring [26,27]. Increased H3K9 acetylation associated with decreased sirtuin 6 (SIRT6) deacetylases in the nucleus of male mouse sperm caused by high-fat diet is associated with increased DNA damage [28].…”
Section: Transgenerational Transmission Of Epigenetic Modificationsmentioning
confidence: 99%